2022
DOI: 10.1111/scs.13130
|View full text |Cite
|
Sign up to set email alerts
|

Hospital and homecare nurses' experiences of involvement of patients and families in transition between hospital and municipalities: A qualitative study

Abstract: Background: Involving patients and families in nursing care is essential to improve patients' health outcomes. Furthermore, families play an essential role in supporting patients by helping nurses understand the patient's everyday life. However, families also need support. Involvement of patients and families is especially important when patients are transferred between hospital and home as transitions heighten the risk of compromising quality and safety in care. However, no consensus exists on how to involve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Other studies show the same. IT systems do not adequately support cross‐sectoral communication, and communication is often complicated due to different organisational workflows and rules on what is shared [24–26]. In addition, the use of different language forms in written communication, both in our study and in other studies, is associated with risks of misunderstandings and medication errors [21].…”
Section: Critical Interpretation and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other studies show the same. IT systems do not adequately support cross‐sectoral communication, and communication is often complicated due to different organisational workflows and rules on what is shared [24–26]. In addition, the use of different language forms in written communication, both in our study and in other studies, is associated with risks of misunderstandings and medication errors [21].…”
Section: Critical Interpretation and Discussionmentioning
confidence: 94%
“…Similarly, other studies have shown that personal contact between nurses in the two sectors is conducive to collaboration on patient admission and discharge [21, 22] and that lack of personal contact is considered an obstacle to good collaboration [23, 24].…”
Section: Critical Interpretation and Discussionmentioning
confidence: 97%